A New Edition of “Punishment and Social Structure” Thirty-Five Years Later: A Timely Event - Melossi, Dario (Social justice, 2003)
Part of a special issue on race, security, and social activism in the U.S. A timely new edition of Georg Rusche and Otto Kirchheimer's 1939 Punishment and Social Structure, reissued in 1968, has been published in 2003. Studies arising from it are discussed, and possible methods for expanding Rusche's research tradition to further the understanding of the social and economic context of penal developments are outlined.